The causes of terrorism in Malaysia - Zul Kepli, Mohd Yazid (Universitas Muhammadiyah Yogyakarta, 2017)
15 years after the declaration of ‘War on Terror’, terrorist groups have not been stopped and de-feated. Instead, unprecedented increase of terrorist attacks occurred worldwide, greatly accelerated by wars and armed conflict in Iraq, Afghanistan, Pakistan, Palestine, Chechnya, Lebanon, Libya and Syria. By the end of year 2016, almost 300 Malaysians and foreigners had been detained by Malaysian authori-ties due to links with terror groups like ISIS. Those arrested includes professionals, lecturers and even policemen. The efforts to combat terrorism is usually limited to building a coalition of military allies, to educate the public, to fortify public spaces with improved securities, to combat terrorism financing and to make better use of the expertise of technology giants especially those in the United States, Korea, France and Canada to help governments enhance security and prevent attacks and to increase monitoring and surveillance. The problem with this approach is that it is dealing with the symptoms rather than addressing the illness. To address the illness, the root causes must be identified. This article analyzes the causes of terrorism in Malaysia. The causes from micro, meso and macro level are scrutinized. Radicalization, political reasons, religion reasons, economic and social reasons and psychological reasons are analyzed further andreviewed.